The outcome of liver resections for hepatoblastoma in children: a 10-year experience from cancer dedicated institute - Sajid Ali; Umair Ahmed; Areej Muhammad Salim; Tariq Latif; Muhammad Ali Sheikh (Journal of the Pakistan Medical Association, 2025)
Objective: To review the comprehensive experience of surgical and oncological management of paediatric hepatoblastoma with 5-year survival outcome. Method: The retrospective study was conducted at the Department of Surgical Oncology, Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data from 2011 to 2020 of primary hepatoblastoma patients aged up to 18 years. Demographic details, size and site of the primary hepatic mass, tumour markers, radiological findings, PRE-Treatment Extent of tumour staging, treatment provided, histopathological and surgical details, and outcomes were assessed. Disease-free survival and overall survival were focussed upon. Data was analysed using SPSS 20. Results: Of the 60 patients with mean age 2.0+1.54 years, 32(53%) were inoperable. The remaining 28(47%) patients underwent liver resection with a mean operative time of 270±118.41 minutes. Right hemi hepatectomy was performed in 14(50%) patients and the most common histology was epithelial foetal type in 16(57.1 %) patients. The five-year disease-free survival was 62%, while the five-year overall survival was 82%. Conclusion: The survival rate of paediatric hepatoblastoma patients who underwent liver resections was within the acceptable range. Key Words: Hepatoblastoma, Liver resection, Children, Outcome.